Productive versus receptive L2 knowledge of polysemous phrasal verbs: A comparison of determining factors. (December 2020) - Sonbul, Suhad; Salam El-Dakhs, Dina Abdel; Al-Otaibi, Hind
Abstract: This study examines factors that might determine EFL learners' receptive and productive knowledge of polysemous phrasal verbs. The factors include (1) raw phrasal verb frequency, (2) sense-based phrasal verb frequency, (3) entrenchment or individual word frequency, (4) sense opacity, (5) L2 estimated proficiency, and (6) the amount and type of L2 exposure. Sixty EFL learners (L1 Arabic) in Saudi Arabia were administered productive (gap-fill) and receptive (multiple-choice) tests assessing their knowledge of 100 phrasal verb senses. The participants knew almost a third of the 100 senses productively but half of these receptively. Mixed-effects modelling results show that on the productive side, the strongest predictor was corpus-derived frequency (both raw and sense-based), followed by opacity, estimated proficiency and the time spent watching films/videos/TV in English. On the receptive side, only sense-based frequency, opacity, estimated proficiency, and particle frequency predicted knowledge. These results have important implications for the learning and teaching of polysemous phrasal verbs in the EFL context, as they identify factors that might make a phrasal verb sense worthy of teaching time and effort.